ANALISIS KADAR D-DIMER PADA PASIEN STROKE ISKEMIK DAN HEMORAGIK DI RSUD SULTAN IMANUDDIN - Yuliyanti; Hidayati, Larantika; Romaidha, Iqlila; Arifin, M. Zainul (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2024)
Stroke is a neurological cerebrovascular disorder caused by disruption of blood supply to the brain and is a leading cause of disability worldwide. 15 million people worldwide experience stroke each year. Stroke is divided into two types, namely ischemic stroke and hemorrhagic stroke. D-dimer is a fibrin degradation product that indicates an impaired fibrinolysis coagulation system. This study aimed to analyze the results of D-dimer examination in patients with ischemic stroke and hemorrhagic stroke at Sultan Imanuddin Hospital, Pangkalan Bun. This study is quantitative analytical with a cross-sectional design. The sampling technique used was purposive sampling. The study sample was 29 ischemic stroke patients and 14 hemorrhagic stroke patients from January - December 2023. Examination of D-dimer levels using the Immunoturbidimetry assay method with the Automated Blood Coagulation Analyzer SYSMEX CS-2100i with a normal limit value of <0.55 mg / L. The results of the study showed that the average D-dimer level of respondents with ischemic stroke was 6.11 mg/L. In comparison, in hemorrhagic stroke, it was 4.8 mg/L and the statistical test results obtained a p-value = 0.378 so that H0 was accepted and Ha was rejected. This study concluded that 1) the average D-dimer level in ischemic stroke patients was 6.11 mg/L with the results showing that most of D-dimer levels being abnormal, 2) the average D-dimer level in hemorrhagic stroke patients was 4.8 mg/L with the results showing that almost all D-dimer levels being abnormal, 3) there was no significant difference between D-dimer levels in ischemic stroke patients and hemorrhagic stroke patients. Keywords: d-dimer, hemorrhagic stroke, ischemic stroke, stroke, thrombus